Diversity and distribution of stream fishes of Pulau Langkawi, Malaysia - Izzati Adilah Azmir,; Abdullah Samat, (Universiti Kebangsaan Malaysia, 2010)
Fishes from five streams in Gunung Machinchang and six streams in Gunung Raya areas of Pulau Langkawi were surveyed with the aim to investigate their diversity and distribution. Fish samples were collected from 23rd to 29th November 2007. Samplings took place along the 50 m reach of each of the site using an electrofisher and scoop nets. A total of 619 individuals of fish comprising 27 species and 14 families were recorded. Sixty-six percent from the taxa listed were of the cyprinids and Puntius binotatus was the most abundant species. Carassius auratus auratus was recorded for the first time in Pulau Langkawi. Streams of the Gunung Machinchang area were dominated by secondary freshwater fish species, but in the Gunung Raya area the streams were dominated by primary freshwater fish species. The highest diversity of fish was recorded for Sg. Kubang Badak with Simpson Index Ds = 0.838 and the lowest was for Sg. Perangin with Ds = 0.450. The highest evenness index of fish species was detected for Sg. Temurun with Es = 0.684 and the lowest was for Sg. Perangin with Es = 0.299. Species overlapping between streams of the two areas was 9.6%.